Triassic stratigraphy and general geology of the country around Fleming Fjord (East Greenland) - Grasmück, K.; Trümpy, Rudolf (Meddelelser om Grønland, 1969)
Geological description of the country to the NW of Fleming Fjord (71°45’ N, 23° W): Kap Biot and Kap Seaforth, and to the SE of the fjord: Wegener Halvø, with special emphasis on Triassic stratigraphy. The lowermost Triassic formation (Wordie Creek fm.) can be subdivided biostratigraphically into several ammonite zones. The two higher formations consist of poorly fossiliferous red beds; the Mt. Nordenskiöld formation is understood to comprise the newly defined Paradigm a member (arkose) and Solfaldsdal member (red mudstones, shales with gypsum), the Cape Biot fm. the Cape Seaforth member (variegated shales with gypsum), the Fleming Fjord member (massive red mudstones) and the Ørsted Dal member (shales and sandstones). Detritus was mainly derived from the E. The complex fault pattern of Wegener Halvø is described; a large NW-hading normal fault runs along Fleming Fjord. Broad anticlines and narrower synclines to the NE of it are probably subordinate to this fault.